Stable Isotope Glaciology. - Dansgaard, W.; Johnsen, S. J.; Clausen, H. B.; Gundestrup, N. (Meddelelser om Grønland, 1973)
The development of the ice core drilling technique has led to a broad variety of studies reaching far beyond glaciology itself. Radioactive and stable isotope analyses of polar ice cores are particular promising. Under cold climatic conditions, the relative concentration (δ) of the heavy stable isotopes oxygen-18 and deuterium in precipitation mainly depends on the temperature of formation. This leads to a geographical δ -distribution and, at a given location, δ variations in phase with seasonal and climatic changes. Under favorable conditions informations may be obtained about present and past changes of climatic and ice flow parameters. However, isotopic homogenization in firn and ice delimits the application of the method, particularly on temperate glaciers and in low accumulation areas. Furthermore, in cases of unstable ice sheets, the climatic component in δ profiles is difficult to separate from the effect of surface altitude changes. The Mid Greenland ice sheet seems to render the most favorable conditions for stable isotope studies on deep ice cores. The Greenland Ice Sheet Program, initiated in 1971, is an international joint effort to extract paleoclimatic and other geophysical informations contained in the ice sheet. Several drillings to 400-500 m depth will be performed in the coming years as precursors of drillings to bedrock in the last half of the 1970 'ies.